2008
DOI: 10.1136/thx.2007.085423
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced pulmonary leptin expression in patients with severe COPD and asymptomatic smokers

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
76
2
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 43 publications
4
76
2
4
Order By: Relevance
“…Using immunohistochemistry, we show for the first time leptin localization in lung tissue of mice, revealing leptin expression in BECs, pneumocytes, alveolar macrophages, and bronchial and vascular smooth muscle cells. The findings of the current study are corroborated by our clinical data that showed that BECs, pneumocytes, and macrophages are a rich source of leptin in human peripheral lung (6). Moreover, the current murine study and our previous human study examining lung tissue and (primary) cell cultures together convincingly demonstrate that smoke is a trigger FIGURE 7.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Using immunohistochemistry, we show for the first time leptin localization in lung tissue of mice, revealing leptin expression in BECs, pneumocytes, alveolar macrophages, and bronchial and vascular smooth muscle cells. The findings of the current study are corroborated by our clinical data that showed that BECs, pneumocytes, and macrophages are a rich source of leptin in human peripheral lung (6). Moreover, the current murine study and our previous human study examining lung tissue and (primary) cell cultures together convincingly demonstrate that smoke is a trigger FIGURE 7.…”
Section: Discussionsupporting
confidence: 78%
“…Leptin was originally described as an adipocyte-derived hormone involved in regulating the balance between food intake and energy expenditure by activating its functional receptor (Ob-Rb) (7) in the hypothalamus (8). Recent studies reported that leptin secretion not only by adipocytes but also by various epithelial cell types, including bronchial epithelial cells (BECs) (6,9) and type II pneumocytes (6). The structure of leptin and its receptor classify leptin as a type I cytokine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking is associated with inflammation and previous studies have shown elevated levels of systemic inflammatory markers, such as WBC count, CRP and fibrinogen, in active smokers (32). This is also true for leptin, which was found to increase in asymptomatic smokers (33). All these data raise the possibility that the high smoking prevalence among controls, might have masked the ongoing systemic inflammation in bronchiectasis patients of our cohort.…”
mentioning
confidence: 47%
“…We found evidence of leptin and leptin receptor expression within airway epithelium. Previous reports have also shown that leptin and leptin receptor are expressed in airway epithelium (24), and bronchial expression of leptin is increased in chronic obstructive pulmonary disease (25,26). Leptin seems to be involved in embryonic lung growth and maturation (27,28), and in fibroproliferative responses in the lung to bleomycin (29).…”
Section: Discussionmentioning
confidence: 99%